Two colors at the SASE3 line of the European XFEL: Project scope and first measurements - Serkez S.; Geloni G.; Gerasimova N.; Grünert J.; Karabekyan S.; Koch A.; Laksman J.; Maltezopoulos T.; Mazza T.; Meyer M.; Tomin S.; Decking W.; et al. (My University, 2022)
The European XFEL is a high-repetition rate facility that generates high-power SASE radiation pulses in three beamlines. A joint upgrade project, with Finnish universities, to equip the SASE3 beamline with a chicane has been recently approved to generate two SASE pulses with different photon energies and temporal separation. In this work we report the status of the project, its expected performance, and recent experimental results. Additionally, we discuss methods to diagnose the properties of the generated radiation.The European XFEL is a high-repetition rate facility that generates high-power SASE radiation pulses in three beamlines. A joint upgrade project, with Finnish universities, to equip the SASE3 beamline with a chicane has been recently approved to generate two SASE pulses with different photon energies and temporal separation. In this work we report the status of the project, its expected performance, and recent experimental results. Additionally, we discuss methods to diagnose the properties of the generated radiation.The European XFEL is a high-repetition rate facility that generates high-power SASE radiation pulses in three beamlines. A joint upgrade project, with Finnish universities, to equip the SASE3 beamline with a chicane has been recently approved to generate two SASE pulses with different photon energies and temporal separation. In this work we report the status of the project, its expected performance, and recent experimental results. Additionally, we discuss methods to diagnose the properties of the generated radiation.The European XFEL is a high-repetition rate facility that generates high-power SASE radiation pulses in three beamlines. A joint upgrade project, with Finnish universities, to equip the SASE3 beamline with a chicane has been recently approved to generate two SASE pulses with different photon energies and temporal separation. In this work we report the status of the project, its expected performance, and recent experimental results. Additionally, we discuss methods to diagnose the properties of the generated radiation.The European XFEL is a high-repetition rate facility that generates high-power SASE radiation pulses in three beamlines. A joint upgrade project, with Finnish universities, to equip the SASE3 beamline with a chicane has been recently approved to generate two SASE pulses with different photon energies and temporal separation. In this work we report the status of the project, its expected performance, and recent experimental results. Additionally, we discuss methods to diagnose the properties of the generated radiation.The European XFEL is a high-repetition rate facility that generates high-power SASE radiation pulses in three beamlines. A joint upgrade project, with Finnish universities, to equip the SASE3 beamline with a chicane has been recently approved to generate two SASE pulses with different photon energies and temporal separation. In this work we report the status of the project, its expected performance, and recent experimental results. Additionally, we discuss methods to diagnose the properties of the generated radiation.
Proceedings of the 39th International Free-Electron Laser Conference